Penerapan Metode MABAC untuk Menentukan Café Tongkrongan Anak Muda Terbaik - Suratman, Amanda Putri; Larasati, Larasati; Anggiani, Poppy Hanna; Batubara, Ela Roza (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Cafés serve not only as a place to enjoy coffee, but also as a forum for social interaction, discussion, and relaxation, especially for the younger generation who are increasingly embracing cafes as part of their lifestyle. In this context, choosing the right cafe is crucial so that the experience is not only satisfying in terms of taste, but also in terms of comfort and atmosphere. This study aims to determine the best cafes for gatherings in Pematangsiantar City using the Multi-Attributive Border Approximation Area Comparison (MABAC) method in a Decision Support System (DSS). This method is used because it can handle decision-making involving multiple criteria objectively and systematically. Seven main criteria were analyzed: price, taste, facilities, atmosphere, service, quality of ingredients, and cleanliness. A total of seven popular cafes in the city were evaluated based on these criteria. The calculation results showed that Inhaven Specialty Coffeebar obtained the highest score of 1.1456829 and was named the best cafe. These findings prove that the MABAC method can provide accurate recommendations and help consumers, especially young people, in choosing an ideal and enjoyable gathering place.